Are prudent monetary and fiscal policy drivers of FDI inflows? - Helder Ferreira de Mendonça; Bruno Pires Tiberto (Latin American Journal of Central Banking (LAJCB), 2024)
Emerging Market and Developing Economies (EMDE) countries are the leading destinations of Foreign Direct Investment (FDI). We investigate whether prudent monetary and fiscal policy through indicators that reflect the expectations concerning the central bank's commitment to a target and the sustainability of government finance affects FDI inflows. Based on a large sample of 75 EMDE countries from 1990 to 2019, we provide empirical evidence through panel data analysis that prudent macroeconomic policies are an essential driver of FDI inflows. The findings support the view that using prudent monetary and fiscal policy can help enhance FDI inflows in EMDE countries.
Keywords: E63; F21; 023; 330; Central bank credibility; Foreign direct investment; Inflation targeting; Macroeconomic stability; Public debt; Risk for budget balance